“Characterization of COX-2 gene using RNA based technique in endometrial epithelial cells of buffalo (Bubalus bubalis)” : Characterization of COX-2 gene in endometrial epithelial cells of buffalo - das, dayal nitai; Dumne, Pravinkumar Ram; PAUL, DIPANKAR; Gnanasekaran, Shanmugapriya; Mondal, Sukanta; Mor, Avantika; Ramesha , Kerekoppa P; SIVARAM, MUNIANDY (Indian Journal of Dairy Science, 2025)
Cyclooxygenase-2 (COX-2), also known as prostaglandin-endoperoxide H synthase-2 plays a vital role in various reproductive events including prostaglandin biosynthesis. The present study has been reported towards molecular characterization of COX-2 gene (PTGS2 gene) in buffalo endometrium. Non-pregnant buffalo uteri were collected from the local abattoir immediately after slaughter and total RNA was extracted. First strand cDNA was synthesized from approximately 2 µg total RNA using iScript cDNA synthesis kit. Following cDNA synthesis, PCR amplification of cDNA was carried out using COX-2 gene specific primers. To determine the optimum conditions, different concentrations of MgCl2, template DNA, Taq DNA polymerase, primers, dNTPs as well as different cycling programmes were analysed. Reproducible amplification pattern was obtained using 2 µl cDNA template (50 ng/µl), 2.5 µl 10X Taq Buffer, 0.5 µl dNTP (50 mM), 2.5 µl MgCl2 (25 mM), 0.5 µl each primer (10 pM/µl), 0.1 µl Phusion DNA polymerase (5 U/µl) and nuclease-free water. After initial denaturation at 98°C for 3 min, 30 cycles of amplification were carried out under the following conditions: denaturation at 98°C for 45 sec, annealing at 59°C for 30 sec, initial extension at 72°C for 90 sec and final extension at 72°C for 10 min. The 449 bp PCR product was checked on 1% agarose gel to verify the amplification of the target region. The optimum annealing temperature for the primers was found to be 59°C for specific amplification of 449 bp. The purified PCR amplified product (449 bp) was sequenced using COX-2 gene specific primers. Nucleotide sequence analysis of PCR amplified product exhibited 100 percent identity with the reference sequence of Bubalus bubalis COX-2 gene using Clustal Omega Multiple Sequence Alignment Tool. Based on above findings, it is concluded that the optimized PCR conditions and the buffalo COX-2 gene specific primers can be useful in pursuing further gene expression studies to explore the function of COX-2 gene in buffalo.